Sustainable forest management in Cameroon needs more than approved forest management plans. - Cerutti, P.O.; Nasi, Robert; Tacconi, L. (2008)
One of the main objectives of the 1994 Cameroonian forestry law is to improve the management of production forests by including minimum safeguards for sustainability into compulsory forest management plans. As of 2007, about 3.5 million hectares (60%) of the productive forests are harvested following the prescriptions of 49 approved management plans. The development and implementation of these forest management plans has been interpreted by several international organizations as long awaited evidence that sustainable management is applied to production forests in Cameroon. Recent reviews of some plans have concluded, however, that their quality was inadequate. This paper aims at taking these few analyses further by assessing the actual impacts that approved management plans have had on sustainability and harvesting of commercial species. We carry out an assessment of the legal framework, highlighting a fundamental flaw, and a thorough comparison between data from approved management plans and timber production data. Contrary to the principles adhered to by the 1994 law, we find that the government has not yet succeeded in implementing effective minimum sustainability safeguards and that, in 2006, 68% of the timber production was still carried out as though no improved management rules were in place. The existence of a number of approved management plans cannot be used a proxy for proof of improved forest management.